Fatal Renal Mucormycosis in an Apparently Healthy Young Man: A Case Report With Review of Literature. (21st September 2018) - Rashid, Sameera; Abid, Fatma Ben; Yassin, Aksam; Christner, Martin; Alobaidy, Abdulqadir; Al-Ansari, Abdulla; Akhtar, Mohammed
Abstract: Objectives: Mucormycosis is a rare fungal infection, encountered primarily in immunocompromised patients. It is the third most common angioinvasive fungal infection after candidiasis and aspergillosis. Isolated mucormycosis of the kidney may be seen in patients with diabetes or renal transplantation, but such an occurrence in apparently healthy immunocompetent patients is extremely rare with only a few cases reported in the literature, mostly from India and China. Methods: We present the case of a 35-year-old Indian male with no known comorbidities who presented with a 4-day history of left flank pain, hematuria, and fever, followed by nausea, vomiting, and constipation. Computerized tomography (CT) of abdomen showed left kidney upper and mid-pole lobar nephronia complicated by infarction. Left nephrectomy revealed a distorted left kidney that, on microscopic examination, showed entirely necrotic and hemorrhagic renal parenchyma with marked acute inflammation and abscess formation. Within many of the necrotic areas, aseptate fungal hyphae, suggestive of mucor, were noted. Some of the blood vessels were thrombosed and contained aggregates of the fungal hyphae within the lumina and invading vessel walls. Antifungal treatment was started, but the patient's condition continued to deteriorate, and the follow-up CT scan showed multiple levels of vascular occlusion, involving the mesenteric vessels as well as contralateral kidney infarction. These findings were suggestive of dissemination of the fungal infection. The patient developed generalized edema and renal and respiratory failure and died on 20th day of hospitalization. PCR study on a tissue block from nephrectomy specimen identified the fungus as Apophysomyces elegans . Conclusion: This case report serves to highlight the possibility of fungal infection, especially A elegans, in the setting of isolated renal infection even in immunocompetent patients. These infections, unless treated early, may progress rapidly and have a high mortality rate.